2018
DOI: 10.1007/978-3-319-72026-5_1
|View full text |Cite
|
Sign up to set email alerts
|

Science for Loss and Damage. Findings and Propositions

Abstract: The debate on "Loss and Damage" (L&D) has gained traction over the last few years. Supported by growing scientific evidence of anthropogenic climate change amplifying frequency, intensity and duration of climate-related hazards as well as observed increases in climate-related impacts and risks in many regions, the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Separate from the ten agreements, the UN SDG framework, adopted in 2015, has emerged as a key driver to enhance sustained observing and response at the global scale (Steffen et al 2018 ). The SDGs are particularly relevant in helping to advance and align concerted action in regions of concern, such as the Arctic, low-lying island nations, and other areas under near-term threat (Mechler et al 2019 ). We compared the CBM questionnaire responses with the 169 SDG targets for the 17 SDG goals and found that Arctic CBM programs contribute to achieving 16 of the 17 SDGs in the Arctic.…”
Section: Community-based Environmental Monitoring: Perspectives From the Arcticmentioning
confidence: 99%
“…Separate from the ten agreements, the UN SDG framework, adopted in 2015, has emerged as a key driver to enhance sustained observing and response at the global scale (Steffen et al 2018 ). The SDGs are particularly relevant in helping to advance and align concerted action in regions of concern, such as the Arctic, low-lying island nations, and other areas under near-term threat (Mechler et al 2019 ). We compared the CBM questionnaire responses with the 169 SDG targets for the 17 SDG goals and found that Arctic CBM programs contribute to achieving 16 of the 17 SDGs in the Arctic.…”
Section: Community-based Environmental Monitoring: Perspectives From the Arcticmentioning
confidence: 99%
“…2. This paper adopts the classification of losses and damages as discussed by Mechler et al (2019), p.11, Table 1.1. : avoided -L&D that can and will be avoided by climate change mitigation and adaptation; unavoidedavoidable L&D that is not/will not be addressed due to financial, technical and political constraints; unavoidable -L&D that cannot be avoided through further mitigation and adaptation measures.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, important points for consideration in climateaware planning are that rapid and slow onset events are interlinked (UNFCCC, 2012), and that there are limits to adaptation (Klein et al, 2014) and consequently, avoided, unavoided and unavoidable losses and damages from climate change (initially classified by Verheyen and Roderick (2008) and further developed by Mechler et al (2019)). For instance, an increased frequency and/or intensity of recurring events like floods and droughts amplifies the risk of irreversible impacts like loss of productive land and biodiversity.…”
Section: Assess and Acknowledge Climate-related Risks And Uncertainties To Create A Long-term Strategic Outlookmentioning
confidence: 99%
“…L&D also presents a range of ethical and global political issues as it narrates the questions of liability and compensation for climate change-induced losses and damages (James et al, 2019). Despite growing scientific advancements, the debate is currently more extensive and prolonged, while the strong policy direction and norms of compensatory justice remain unclear and disputed (Mechler et al, 2019). It is essential to develop a separate definition to assess the local level loss and damage incurred from a particular climatic event by considering the diverse global and local context (Van der Geest, 2018).…”
Section: Understanding Local Level 'Loss and Damage'mentioning
confidence: 99%